Emotional, Psychological, and Cognitive Changes Throughout the COVID-19 Pandemic in Italy: Is There an Advantage of Being an Older Adult? - Carbone, Elena; Palumbo, Rocco; Sella, Enrico; Lenti, Graziana; Di Domenico, Alberto; Borella, Erika (Frontiers in Aging Neuroscience, 2021)
Introduction: The study examined age-related differences between young and older adults’ emotional and psychological experience as well as cognitive functioning throughout different phases of the COVID-19 pandemic in Italy. Materials and Methods: Participants were interviewed by phone when confined at home during the national lockdown (T1-May 2020; N = 138 young adults; N = 119 older adults) and after the first wave of contagions, when restrictions were discarded (T2-September 2020; N = 52 young adults; N = 59 older adults). A sub-sample also participated in a third assessment (T3-December 2020). Participants completed questionnaires assessing their emotional and psychological functioning (i.e., positive and negative affect, perceived social and emotional loneliness, resilience) along with memory tasks (Backward Digit Span task and words list recall). Results: Although individuals reported less positive and more negative emotions during the lockdown than at T2, results showed that older adults displayed overall fewer negative emotions and greater resilience than young adults. The latter were those who reported feeling more emotionally lonely when compared to their older counterpart during the lockdown than afterward. Older adults’ advantage in emotional and psychological functioning was also confirmed 7 months after the national lockdown. Only age-related differences in favor of young adults for the memory tasks were found. The measures of interest were also susceptible to mood and/or concerns of COVID-19 effects. Discussion: These findings further highlight the age-related advantage of older adults managing the emotional and psychological experience even when facing an unexpected, prolonged, and unpredictable, stressful life event such as the COVID-19 pandemic.